A 406-year non-growing-season precipitation reconstruction in the southeastern Tibetan Plateau - M. Keyimu (Copernicus Publications, 2021)
Trees record climatic conditions during their growth, and tree rings serve as proxy to reveal the features of the historical climate of a region. In this study, we collected tree-ring cores of hemlock forest (Tsuga forrestii) from the northwestern Yunnan area of the southeastern Tibetan Plateau (SETP) and created a residual tree-ring width (TRW) chronology. An analysis of the relationship between tree growth and climate revealed that precipitation during the non-growing season (NGS) (from November of the previous year to February of the current year) was the most important constraining factor on the radial tree growth of hemlock forests in this region. In addition, the influence of NGS precipitation on radial tree growth was relatively uniform over time (1956–2005). Accordingly, we reconstructed the NGS precipitation over the period spanning from 1600–2005. The reconstruction accounted for 28.5 % of the actual variance during the common period of 1956–2005. Based on the reconstruction, NGS was extremely dry during the years 1656, 1694, 1703, 1736, 1897, 1907, 1943, 1982 and 1999. In contrast, the NGS was extremely wet during the years 1627, 1638, 1654, 1832, 1834–1835 and 1992. Similar variations of the NGS precipitation reconstruction series and Palmer Drought Severity Index (PDSI) reconstructions of early growing season from surrounding regions indicated the reliability of the present reconstruction. A comparison of the reconstruction with Climate Research Unit (CRU) gridded data revealed that our reconstruction was representative of the NGS precipitation variability of a large region in the SETP. Our study provides the first historical NGS precipitation reconstruction in the SETP which enriches the understanding of the long-term climate variability of this region. The NGS precipitation showed slightly increasing trend during the last decade which might accelerate regional hemlock forest growth.